Learning Outcomes for a Business Information Systems Undergraduate Program - ELMALEH, Joelle (Institutional Knowledge at Singapore Management University, 2008)
We present a learning outcomes framework for an Information Systems (IS) undergraduate program. This framework includes a supporting software application that goes beyond any other attempt reported to date to integrate learning outcomes into program-wide and course-wide curriculum development, ongoing curriculum redesign, and student learning support. The Learning Outcomes Management System (LOMS) described here is a first-of-a-kind information system created as part of implementing a program-wide learning outcomes framework in a university setting. Our learning outcomes framework is distinct in that 1) it is based on a three-level hierarchically structured definition of learning outcomes that consistently apply to both the entire IS program as well as to each individual IS course; 2) customization for specific courses is easily done without requiring the drafting of new learning outcomes; 3) the dean’s office and faculty use the learning outcomes framework to design, monitor, and revise both the entire IS curriculum as well as each individual course on an ongoing basis; 4) when students assess their own capabilities against our school’s learning outcomes, it is done on a more global basis (versus a course specific basis), based on what students have done in their IS coursework, in their business, social science, and liberal arts coursework, as well as in their internships and extra-curricular activities; and 5) we incorporate the framework into a school-wide information system, LOMS, which has an application and supporting interface customized for faculty’s needs, students’ needs, and employers’ needs.